Perlindungan Hukum Terhadap Kreditur Fidusia - Naway, Dian Rizqi Oktaria; Badu, Lisnawaty W.; Mantali, Avelia Rahma Y. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Fiduciary is a term that has long been known in Indonesian. The law that specifically regulates this matter, namely UUJF also uses the term "fiduciary". Thus, the term "fiduciary" is already an official term in our legal world. However, sometimes in the Indonesian language this fiduciary is also referred to as "transfer of ownership rights in trust". The purpose of this study is to determine the legal protection of fiduciary creditors. The type of research used is normative juridical research with a statutory approach and a case approach, which is supported by data obtained from library data including books, laws and regulations, and court decisions, and in this case the data is processed using qualitative analysis. Based on research results In line with the principle of providing legal certainty, UUJF adopts the principle of registration of fiduciary guarantees. The registration is expected to provide legal certainty to fiduciary givers and recipients as well as to third parties. According to Article 1 number 6 UUJF it is stated "Fiduciary Recipients are individuals or corporations who have receivables and their payments are guaranteed by a fiduciary guarantee". In the Fiduciary Guarantee Law to create protection for creditors, the Fiduciary Guarantee agreement must first be registered, as stipulated in Article 11 of the Fiduciary Guarantee Law, registration as fulfillment of the principle of publicity, imposition of fiduciary guarantees only with a notarial deed without registration is not will give birth to preferential rights to creditors receiving fiduciary positions. The creditor receiving the fiduciary receivables is the holder of the guarantee, while the authority as the owner is the authority that is still related to the guarantee itself (limited in nature), because the object of the fiduciary guarantee is not directly under his control.